Aspergillus fumigatus spondylodiscitis with bilateral psoas abscess in a renal transplant patient with pulmonary tuberculosis : A rare case report - Tv, Ravikumar; Rao, Raghvendra; Grover, Amit; Gadi, Daksh (International Journal of Medicine, 2015)
Background: Aspergillus spondylodiscitis is increasingly described in immune-compromised patients. Its diagnosis is challenging and its delay results in high mortality and morbidity in view of its relative infrequency and the non- specific clinical signs and symptoms.Case report:We report a case of thoracic spondylodiscitis caused by Aspergillus fumigatus in a patient of renal transplantation and with proven pulmonary tuberculosis.Conclusion:We reiterate that transplantist and the treating physician should have high grade of suspicion for the invasive Aspergillosis even when the patient complains of vague non-specific back pain, and aggresively aim to rule out fungal infection. Early surgical debridement and antifungal therapy to be executedto prevent rapid progression of invasive aspergillosis and neurological damage.